Alignment of Strategic Priorities at the Functional Level and Business Level with Manufacturing Performance - Tarigan, Robinson (Jurnal Widya Manajemen & Akuntansi, 2005)
This is a study of literature to propose the influence of the perceptions of general managers and manufacturing managers concerning manufacturing priorities of their business units (alignment) on manufacturing unit performance.